Answer:
2x + 3y = 4
Step-by-step explanation:
The standard form:
Ax + By = C
So from the given form, arrange it to the standard form.
First, simplify the form by distribution.
y + 6 = -2/3(x - 11)
y + 6 = -2/3x + 22/3
Next, you make the fractions into whole by multiplying both sides by 3(this would eliminate all fractions).
(3)y + 3(6) = 3(-2/3x) + 3(22/3)
3y + 18 = -2x + 22
Now, arrange the "Ax" and the "C's".
3y + 18 = -2x + 22
2x + 3y + 18 = 22
2x + 3y = 22 - 18
2x + 3y = 4
Cheers!
By the definition for the absolute value,
![|x-1|=\begin{cases}x-1&\text{for }x\ge1\\-(x-1)&\text{for }x](https://tex.z-dn.net/?f=%7Cx-1%7C%3D%5Cbegin%7Bcases%7Dx-1%26%5Ctext%7Bfor%20%7Dx%5Cge1%5C%5C-%28x-1%29%26%5Ctext%7Bfor%20%7Dx%3C1%5Cend%7Bcases%7D)
![|x+1|=\begin{cases}x+1&\text{for }x\ge-1\\-(x+1)&\text{for }x](https://tex.z-dn.net/?f=%7Cx%2B1%7C%3D%5Cbegin%7Bcases%7Dx%2B1%26%5Ctext%7Bfor%20%7Dx%5Cge-1%5C%5C-%28x%2B1%29%26%5Ctext%7Bfor%20%7Dx%3C-1%5Cend%7Bcases%7D)
So for the compound function
![f(x)=1-|x-1|+|x+1|](https://tex.z-dn.net/?f=f%28x%29%3D1-%7Cx-1%7C%2B%7Cx%2B1%7C)
, there are three intervals to consider. What happens when
![x](https://tex.z-dn.net/?f=x%3C-1)
? when
![-1\le x](https://tex.z-dn.net/?f=-1%5Cle%20x%3C1)
? when
![x\ge1](https://tex.z-dn.net/?f=x%5Cge1)
?
You have
Answer:A) 8 miles
Step-by-step explanation:
8 miles
Answer:
Step-by-step explanation:
Answer:
-30(3+2w)
(-9-6w) ⋅ 10
−20(4.5 + 3w)
Step-by-step explanation: